Risk Factors for Postoperative Neck Complaints After Robot-Assisted Surgery. A Systematic Literature Review - Rommers, Ellis; Jacxsens, Laura; Van Brussel, Naomi; Topsakal, Vedat; De Hertogh, Willem (ENT Updates, 2022)
Background: Robot-assisted and image-guided surgery have become increasingly important because it outperforms human dexterity. For procedures on sub-millimet-ric level, fixing the patient’s head firmly is crucial. Although the neck is not the targetorgan of the operation, it may be at risk of postoperative complaints due to position-ing or fixation. The incidence of postoperative symptoms after head and neck surgery with fixation is hardly reported and probably underestimated, in regards to the life-threatening cranial pathologies for which the surgery was required. Methods: To identify papers on risk factors for postoperative complaints after headand neck surgery, we performed a systematic review. PubMed and Web of Sciencedatabases were searched using predefined in- and exclusion criteria. Meta-analysesand reviews were excluded. Postoperative complaints concerned pain, quality oflife, discomfort, neuropraxia, and musculoskeletal problems. This review is reportedaccording to PRISMA guidelines. Results: Seven eligible studies were identified, only 2 concerned surgery requiring head fixation. The significant risk factors resulting from our analysis were preopera- tive pain (odds ratio=2.19), expected pain (odds ratio=2.15), short-term fear (odds ratio = 1.42), age between 45 and 59 years old (odds ratio = 1.40), pain catastrophizing (odds ratio = 1.21), and female gender (odds ratio = 0.74). Conclusion: Six significant risk factors for iatrogenic postoperative complaints after head and neck surgery have been identified. These risk factors should be consideredas possible confounding factors in future research. Little literature could be found. Upcoming robotic surgeries in the head and neck area pose a clinical need for morespecific studies on postoperative iatrogenic complaints.